2007
DOI: 10.1002/ffj.1822
|View full text |Cite
|
Sign up to set email alerts
|

A selective and sensitive approach to characterize odour‐active and volatile constituents in small‐scale human milk samples

Abstract: A sensitive and selective analytical approach was developed for the characterization of trace volatile and odorous substances in body fluids. The methodology was successfully applied for identification of more than 40 characteristic odorants in human milk. The technique comprises a modified stir bar sorptive extraction system in combination with two-dimensional gas chromatographic separation and parallel mass spectrometric and olfactometric characterization of the analytes. The present study shows that the tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 35 publications
4
45
1
1
Order By: Relevance
“…The presence of secondary products of lipid oxidation, aldehydes, ketones, and alcohols in mother's milk are in accordance with earlier studies (Bingham et al 2003;Buettner 2007;Shimoda et al 2000;Stafford et al 1976). In the studies by Shimoda et al (2000) and Buettner (Buettner 2007), a greater number of unsaturated and longer chain carbonyl compounds were identified in the volatile fraction.…”
Section: Mother's Milksupporting
confidence: 91%
See 4 more Smart Citations
“…The presence of secondary products of lipid oxidation, aldehydes, ketones, and alcohols in mother's milk are in accordance with earlier studies (Bingham et al 2003;Buettner 2007;Shimoda et al 2000;Stafford et al 1976). In the studies by Shimoda et al (2000) and Buettner (Buettner 2007), a greater number of unsaturated and longer chain carbonyl compounds were identified in the volatile fraction.…”
Section: Mother's Milksupporting
confidence: 91%
“…In the studies by Shimoda et al (2000) and Buettner (Buettner 2007), a greater number of unsaturated and longer chain carbonyl compounds were identified in the volatile fraction. In addition, a number of medium chain fatty acids (C 8 -C 12 ) were detected by Shimoda et al (2000), whereas only acetic acid and short chain fatty acids (C 3 -C 5 ) were identified in the present study.…”
Section: Mother's Milkmentioning
confidence: 96%
See 3 more Smart Citations